2020
DOI: 10.3390/nu12071961
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and State of Nutrition of Patients with Gastroenteropancreatic Neuroendocrine Neoplasms

Abstract: Introduction: In recent decades, the number of gastro-entero-pancreatic neuroendocrine neoplasms (GEP-NENs) cases, associated with coexisting metabolic disorders, has been continuously increasing. Patients with progressing neoplastic disease are at a risk of malnutrition. To improve the quality of life of neuroendocrine neoplasms (NEN) patients, the therapeutic approach should be supported by a well-balanced diet. The aim of the study was to analyze the nutritional errors and deficits in a group of GEP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
(60 reference statements)
1
5
0
Order By: Relevance
“…In this regard, the collaboration between multidisciplinary teams that include oncologists, endocrinologists and nutritionists are necessary to identify patients at high risk and to implement physical exercise and specific nutrition prevention programs. In this context, the research team agrees with the recommendations previously published by Kikut et al [ 20 ] for the nutritional management of patients with neuroendocrine tumors where it is proposed that standardizing nutritional care of patients with NETs should be a priority direction in the management of these patients. Due to the heterogeneity of this oncological pathology, the nutritional management of each patient will probably have to be individualized.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In this regard, the collaboration between multidisciplinary teams that include oncologists, endocrinologists and nutritionists are necessary to identify patients at high risk and to implement physical exercise and specific nutrition prevention programs. In this context, the research team agrees with the recommendations previously published by Kikut et al [ 20 ] for the nutritional management of patients with neuroendocrine tumors where it is proposed that standardizing nutritional care of patients with NETs should be a priority direction in the management of these patients. Due to the heterogeneity of this oncological pathology, the nutritional management of each patient will probably have to be individualized.…”
Section: Discussionsupporting
confidence: 78%
“…The prevalence of malnutrition in GEP-NETs patients is not well known to date. However, there are already studies that suggest that patients with GEP-NET have nutritional deficits and that their diet is inadequate [ 20 ]. Some studies have evaluated BMI in patients with GEP-NETs, but the association between nutrition and clinical outcomes has not been consistent in these tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this, it is reasonable to suggest that appropriate nutritional screening should be performed at diagnosis and during follow-up for all patients with NENs, as in other types of cancer [ 1 ]. Additionally, nutritional recommendations, including calorie and protein intake should be provided [ 53 ], and additional oral nutritional supplementation should be started early on for those patients who are malnourished or at risk of malnutrition [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study involving 138 patients with GEP and NET estimated that approximately 68% patients had vitamin D values < 20 ng/mL [68]. In these patients, the observed deficiency can lead to an increased risk of osteoporosis and osteopenia; this risk is further exacerbated by analogous molecules of somatostatin administered to some of these patients, causing a reduced adsorption of vitamin D taken with the diet [69]. It has also been observed that the vitamin D system is deregulated in the pancreas of PDAC patients (Figure 4).…”
Section: Vitamin Dmentioning
confidence: 99%